Lima Langkah Sukses Kepala Sekolah Dalam Membina Akhlak Siswa Di Sekolah Menengah Pertama Kota Solok - Sriwardona, Sriwardona; Yumna (STAI YAPTIP Simpang Empat Pasaman Barat Indonesia in collaboration with International Islamic Studies Development and Research Center (IISDRC), 2023)
Junior High School students in Solok City are directed to participate in prospering the mosque in their neighborhood by participating in religious activities managed jointly by the Regional Government, Education Office, Ministry of Religious Affairs, Religious Teachers, Preachers, Mosque Administrators and parents. In order to make this activity a success, the principal's management is needed, especially in fostering students' morals. The purpose of this study was to analyze the steps taken by schools in fostering the morals of Junior High School students in Solok City. This study used a qualitative method with a case study approach that began with data collection through interviews, observations, and document analysis, then the data was analyzed. The results of the research analysis showed five successful steps for the principal in fostering students' morals: 1) the principal planned the development of students' morals by instructing all teachers to foster morals and including moral development in the learning implementation plan. 2) The principal organizes moral development starting from level 1 moral development carried out by educators and education staff by providing exemplary examples, moral development carried out by the homeroom teacher for the students under his supervision, level 2 moral development carried out by guidance and counseling teachers who cannot be handled by the homeroom teacher, level 3 development of homeroom teachers and guidance and counseling teachers, level 4 moral development of students through collaboration with parents. 3) The principal carries out moral development of students a) directly such as providing exemplary examples, advising and reprimanding undisciplined teachers and b) indirectly moral development carried out by all educators, establishing cooperation with various parties in developing morals of students such as cooperation between Islamic religious education teachers and general study teachers. 4) The principal controls the development of morals of students through all teaching teachers. Teachers have the responsibility to guide, foster and direct students to have good morals. In this case, the teacher conveys the results of his development to the principal through the student representative. 5) The principal evaluates students' moral development by administering punishments or sanctions in collaboration with the students' parents. The implications of this research can provide principals and educators with insights into how to foster students' moral development. This research can serve as a foundation for other researchers to conduct further research in different contexts and on different issues.